2013
DOI: 10.1021/mp4003442
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Desorption-Controlled Release of Fluorescent Dye and Vitamin from Solution-Blown and Electrospun Nanofiber Mats Containing Porogens

Abstract: In the present work, a systematic study of the release kinetics of two embedded model drugs (one completely water soluble and one partially water soluble) from hydrophilic and hydrophobic nanofiber mats was conducted. Fluorescent dye Rhodamine B was used as a model hydrophilic drug in controlled release experiments after it was encapsulated in solution-blown soy-protein-containing hydrophilic nanofibers as well as in electrospun hydrophobic poly(ethylene terephthalate) (PET)-containing nanofibers. Vitamin B2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 72 publications
3
75
1
2
Order By: Relevance
“…In vitro release of a compound encapsulated in insoluble fibers has previously been correlated to the porosity of the fibers 19,20,42 . From those studies it was found that the release was facilitated by a twostep mechanism; desorption of the compound from the nanoporous surface of the fibers, as the rate 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 13 limiting step, followed by diffusion from the fiber matrix into the buffer.…”
Section: Fiber Porosity Was Affected By Interactions With Surfactantmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro release of a compound encapsulated in insoluble fibers has previously been correlated to the porosity of the fibers 19,20,42 . From those studies it was found that the release was facilitated by a twostep mechanism; desorption of the compound from the nanoporous surface of the fibers, as the rate 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 13 limiting step, followed by diffusion from the fiber matrix into the buffer.…”
Section: Fiber Porosity Was Affected By Interactions With Surfactantmentioning
confidence: 99%
“…As a result, only compounds situated at the surface of the fibers were released, as long as the fibers were intact. Modulating the porosity, and thus the surface area, for instance by addition of porogens, such as poly(ethylene glycol), or varying the polymer nature, concentration, or molecular weight, modified the maximum released amount, and also the compound release profile 19,42,43 . In Figure 1 (Figure 2).…”
Section: Fiber Porosity Was Affected By Interactions With Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The mechanism governing drug release kinetics from degradable matrices is complex owing to alterations in polymer phase properties during degradation, causing changes in drug diffusivity and permeability with time. 40 Two representative mechanisms were reported on the release characteristics from nanofibers: one is desorption limited release, [41][42][43] the other is Fickian diffusion (M t /M 1 < 0.6). 38,44,45 In the present work, Fickian diffusion model for M t /M 1 < 0.6 was adopted as follows:…”
Section: Assay Of Antibacterial Ability and Release Behavior Formentioning
confidence: 99%
“…8,11,12 Electrospun fibers have been found to be good candidates for a wide variety of biomedical applications such as cardiovascular stents, 13 wound healing, 14 and the controlled release of active ingredients. [15][16][17] Electrospun drug-loaded fibers have been broadly explored for targeted release, for improving the dissolution rate of poorly water-soluble drugs, and for encapsulating multiple functional components. [18][19][20] The simplest process involves a single needle, and produces monolithic fibers.…”
Section: Introductionmentioning
confidence: 99%